1978
DOI: 10.1044/jshr.2101.151
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Use of Spatial Prepositions in Two- and Three-Dimensional Tasks

Abstract: This study evaluates children’s performance on selected spatial prepositions and determines the age levels these prepositions are acquired in both receptive and expressive language, as revealed in tasks involving both two- and three-dimensional objects. Subjects were 80 children (40 males and 40 females), ranging in age from three years to four years and eleven months. All were native English speakers with no speech, hearing, or neurological disorders, and with normal intelligence. Results indicated a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 0 publications
9
42
0
Order By: Relevance
“…These results differ with researchers (Harris and Strommen, 1972;Kuczaj and Maratsos, 1975) who found that children, ranging in age from 2.6 to 7.5, performed better on tasks that used their bodies as referents than tasks using objects as referents. However, research supports the finding of significantly better performance on object manipulation tasks as compared to picture tasks (Washington and Naremore, 1978).…”
Section: Comparisons By Age Groupsupporting
confidence: 52%
See 2 more Smart Citations
“…These results differ with researchers (Harris and Strommen, 1972;Kuczaj and Maratsos, 1975) who found that children, ranging in age from 2.6 to 7.5, performed better on tasks that used their bodies as referents than tasks using objects as referents. However, research supports the finding of significantly better performance on object manipulation tasks as compared to picture tasks (Washington and Naremore, 1978).…”
Section: Comparisons By Age Groupsupporting
confidence: 52%
“…These researchers have investigated assessment variables such as context (picture, object, no context) and response (self actions, manipulating, pointing) in assessing normal children's understanding and use of prepositions (Harris and Strommen, 1972;Kuczaj and Maratsos, 1975;Wilcox and Palermo, 1975;Silliman, 1979;Levine and Carey, 1982). Most have considered these variables separately, but a few have contrasted a limited number of variables with significant results for some age groups (Ault, Cromer and Mitchel, 1977;Washington and Naremore, 1978). Contrasting a number of these assessment variables across a wider age range could give more information about how normal children understand locative prepositions, and how to best assess this knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prepositions are especially important for understanding the cognitive and linguistic abilities of both the normal hearing and hearing impaired as they are a means of relating the syntactical and semantic components of language (Washington & Naremore, 1978).…”
Section: Chapter II Review Of the Literaturementioning
confidence: 99%
“…Prominent among function words are prepositions. Prepositions integrate the cognitive functions of semantic and syntactic relations associated with the concepts of place and time (Washington & Naremore, 1978).…”
Section: Introductionmentioning
confidence: 99%